The prevalence of circulating S. pneumoniae serotypes in people older than 18 years: healthy carriers, patients with acute otitis media, community-acquired pneumonia, and invasive pneumococcal infections (epidemiological study «SPECTRUM») - Muravyev A.A.; Chagaryan A.N.; Ivanchik N.V.; Kurkova A.A.; Tsvetkova I.A.; Kozlov R.S.; Morozova O.A.; Kirillova G.SH.; Popova L.D.; Moskvitina E.N.; Petrova T.A.; Martyanova N.M.; et al. (Клиническая микробиология и антимикробная химиотерапия, 2019)
Objective.